Comparison of ridge resorption and patient satisfaction in single implant-supported mandibular overdentures with conventional complete dentures: A randomised pilot study - Subin KM; Dheeraj Kumar Koli; Veena Jain; Gunjan Pruthi; Aditi Nanda (Elsevier, 2021)
Purpose: To compare ridge resorption (RR) and patient satisfaction in single implant-supported mandibular overdentures (SIMO) with conventional complete dentures (CCD) over a period of one year. Material and methods: This prospective, randomized trial enrolled 30 completely edentulous participants following inclusion and exclusion criteria. The study was completed by 28 participants. Rehabilitation of 14 participants was done by using SIMO (group I) and CCD (group C) each according to randomization chart. For both the groups, RR was computed in millimeters from residual ridge height measured by using orthopantogram at 6 months (T1), 9 months (T2), and 12 months (T3) at 3 anatomic locations: maxillary posterior (L1), maxillary anterior (L2), and mandibular posterior (L3). Patient satisfaction was evaluated by using Geriatric Oral Health Assessment Index Hindi version (GOHAI-Hi) at 1week and 12 months after denture delivery. Results: At 12 months, minimum RR was observed at L2 of group I (0.62 ​± ​0.20 ​mm) and maximum RR was observed at L3 of group C (1.04 ​± ​0.15 ​mm). Comparison of ridge resorption between group I and group C was statistically significant at T3 (P ​= ​.001 for L1, P ​= ​.006 for L2, and P ​= ​.028 for L3). At T3, in group I, RR was more at L3 than L2 region (P ​= ​.011) and L1 region (P ​= ​.015). Statistically significant difference of GOHAI-Hi scores was observed between group I and group C at end of 12 months (P ​= ​.003). Conclusions: SIMO cause less RR and higher patient satisfaction as compared to CCD and can be recommended with higher predictability of success than CCD.